Analisis Kesulitan Membaca Permulaan Siswa Kelas I Sekolah Dasar - Joko Saputra; Sivina Noviyanti (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2022)
The aim of this research is to describe the initial reading difficulties in reading aloud to grade I students in elementary school. This research was conducted at State Elementary School Number 186/I Sridadi in March 2022. Research data was obtained by conducting observations, interviews and documentation. Data collection aims to see the initial reading difficulties in reading aloud to grade I elementary school students. The approach to this research uses a qualitative approach with a case study type of research. The subjects of this research were class I teachers and class I students at SD Negeri 186/I Sridadi and their parents. The data obtained was then analyzed using the first stage of data reduction, the second stage of data presentation, and the third stage of data verification. The results of the research show how difficult it is to start reading aloud in grade I elementary school students. Class I students at State Elementary School 186/I Sridadi have difficulty reading aloud. The difficulties experienced by students are difficulty in recognizing letters, difficulty reading syllables, difficulty reading words, difficulty reading simple sentences, and difficulty reading with clear pronunciation and intonation. Difficulty reading at the beginning using the reading aloud technique is still experienced by class I students at SDN 186/I Sridadi.